A Graphical Web Tool with DL-based Reasoning Support over Orthogonal Variability Models - Oyarzun, Ángela (2018)
Variability Management is one of the most challenging tasks in a Software Product Line (SPL) development. This is reflected in the way software is developed, maintained and extended. Therefore, automatic variability analysis has emerged in order to validate models in early development stages, avoiding affecting derived products quality. In this work, we present crowd-variability, a novel graphical tool designed for modelling and validating Orthogonal Variability Models (OVM) using Description Logics (DL)-based reasoning services. We describe the tool and demonstrate the usage of the first prototype along with examples of use. Currently, we are working to release the first beta version of crowd-variability.